A Study On The Income Levels Of Patchouli Farmers In Taramanu Tua Village, Tutar District, Polewali Mandar Regency - Mahmud , Mahmud; Andayani, Nining Diah; Rahman, Adiputra (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to analyze the income earned by patchouli farmers in Taramanu Tua Village and to identify the factors that influence their earnings. A qualitative approach was employed using observational methods, with data collected through in-depth interviews with patchouli farmers in the village. A total of 20 patchouli farmers participated as respondents. The findings indicate that the income of patchouli farmers is influenced by several key factors, including land area, fluctuations in patchouli oil selling prices, and high production costs, which encompass plant maintenance, fertilizer purchases, and labor expenses. Although patchouli farming holds considerable potential, price volatility remains a major challenge affecting income stability. Furthermore, the limited land area owned by most farmers restricts their ability to significantly increase production. Therefore, this study recommends several strategies, such as market diversification, improved cost-efficiency in production, and the adoption of more advanced agricultural technologies, in order to enhance the welfare of farmers in Taramanu Tua Village.